ESTABLISHMENT OF INTENSITY MODEL FOR LASER WELDING LINE AND PREDICTION OF FAILURE - ZHAN MinMin; DAI Xin; CAO Shu; YU JingHu (Jixie qiangdu)
According to the welded joints of cold formed hot-rolled automobile structural steel S420 MC and S500 MC, indentation tests on the cross-section were carried out to establish the constitutive relation for melting zone、heat affected zone and base metal. Based on ductile rupture and shear failure, a new failure model（micro failure model） for welding line was proposed, in which Kolmogorov integral equation was used to be a failure criterion taking account into the time correlation and damage accumulation. On the basis of the model, mechanical behaviors of welding line under the condition of impact load were simulated, then compared the results with two other numerical models（macro one-dimensional model and macro three-dimensional model）. The comparison results indicate that the simulation with micro failure model not only gives the uniform strength evaluation, but also can predict the time and area for initial ductile. Micro failure model could reflect the mechanical behaviors of laser welding line under impact load.